Cell surface flip-flop of phosphatidylserine is critical for PIEZO1-mediated myotube formation - Tsuchiya, Masaki; Tanaka, Motomu (Nature Communications, 2018)
Myotube formation by fusion of myoblasts is essential for skeletal muscle formation, but which molecules regulate this process remains elusive. Here authors identify the mechanosensitive PIEZO1 channel as a key element, whose activity is regulated by phosphatidylserine during myotube formation.
Gesehen am 13.06.2019